EFFECTIVENESS OF BIOCHAR AS SOIL AMELIORANT TO INCREASE SMALL SHALLOT BULBS YIELD FROM TRUE SHALLOT SEED (TSS) IN DRYLAND AGROECOSYSTEM - Rahayu, Muji; Pangestuti, Retno (Universitas Tadulako, 2024)
The decline in soil fertility, characterized by extremely low organic matter content, is a common occurrence in agricultural land due to the intensified practices of crop production. These practices often involve the unwise application of chemical fertilizers and a lack of recycling agricultural waste as organic fertilizers. This study aimed to investigate the impact of biochar on the yield of small shallot bulbs grown from true shallot seed (TSS) in a dryland agroecosystem. The experimental trial was conducted using a randomized block design, incorporating two factors: organic amendments (biochar, manure, and biomass) and TSS varieties (Tuk-tuk, Sanren, and Trisula). The results demonstrated that the use of biochar, particularly in the Trisula variety, resulted in the highest production of mini-tubers, with an average of 4.5 tubers per seed. In comparison, the Sanren variety yielded 1.8 bulbs per seed, while the Tuk-Tuk variety yielded 1.2 bulbs per seed. Furthermore, the application of biochar had a positive influence on soil properties, such as increased levels of organic carbon (C- organic), availability of phosphorus (P-available), and cation exchange capacity (CEC) in dry soils. The utilization of biochar as an organic amendment demonstrated its potential to enhance shallot bulb yield, particularly in the Trisula variety, within a dryland agroecosystem.